PERTANGGUNGJAWABAN PIDANA PELAKU ANAK PADA KECELAKAAN LALU LINTAS DENGAN KORBAN ORANG TUA KANDUNG - Nurul Fathiqah Sari (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2023)
Traffic accidents that cause death are problems that are always prominent from time to time. Accidents can happen to anyone, anytime, and anywhere. Moving on from the tragic news of an accident that shocked the public in October 2022 involving a 15-year-old child member of the TNI with the initial AT driving a car and crashing into both of his parents causing death. This study needs to be examined in the aspect of criminal liability to resolve if the intended legal event occurs. The research method used in this research is normative juridical method.